Anti-Sectarian Mission of Holy Cross Brotherhood in Nizhny Novgorod Diocese in 1906-1916 - N. E. Arkhipova (Научный диалог)
The work of the anti-sectarian mission of the brotherhood of the Holy cross in the Nizhny Novgorod diocese, founded in connection with the decree of 1905, which established freedom of religion for sectarians, is considered. It is indicated that at that time a sect was understood as religious association, deviating from the dogmatic teaching of the Orthodox Church (except for the Catholicism, Lutheranism and Anglicanism). It is shown that the Nizhny Novgorod mission conducted polemic conversations, teachings, anti-sectarian conversations at fairs, distributed free leaflets and brochures, organized short-term anti-sectarian courses for clergy, as well as for peasants during fairs. It is noted that the parishes created societies and brotherhoods of Orthodoxy zealots, but they were few. It is shown that during the First world war polemic conversations were replaced with preaching ones, technical novelty was used at meetings with peasants - a lantern with light pictures, in the course of conversations the main emphasis was placed on enlightenment of the Orthodox people of the state Church. The author notes the difficulty of assessing the success of the anti-sectarian mission, since there were no exact data on the number of sectarians, their transitions from Church to sect and back. Along with that the growth of sectarianism caused by the unconscious attitude of the Orthodox people to Church life and apostasy occurred secretly. It is concluded that the work of the anti-sectarian mission was mainly of a preventive nature.